Spreading digital literacy via Minimal English. The concept of ‘class’ in Swift programming language - Bartłomiej Biegajło (LingBaW)
The article aims at providing explications of the concept of a class, as it is implemented in the Swift programming language offered by Apple. The explications are framed in Minimal English, which is based on the theory of Natural Semantic Metalanguage. Detailed analysis of the Swift concept of class leads to four distinct core explications of the programming construct in question and the related feature that Swift classes possess, namely the concept of property. The article’s primary purpose is to offer a more smooth experience with programming, especially with beginners in mind. Their initial exposure to programming might face several challenges due to the complicated digital jargon of the documentation. Minimal English is implemented to ease the learning curve and promote digital literacy as one of the most fundamental skills in today’s world.